Dengue in Costa Rica: the gap in local scientific research - Troyo Rodríguez, Adriana (2006)
Globalization has affected the reemergence of infectious diseases, with increased human travel and trade facilitating the introduction of diseases into new areas and the resurgence of diseases that had been eliminated in some places (1). However, the increased availability of scientific information from various research groups can help in the development of new and improved disease control measures. The combination of scientific research and reliable field assessments that consider different areas of knowledge and different geographic locations (world regions, countries, and communities) is essential for building greater understanding. This combination can also provide evidence that guides prevention and control measures at the local, national, regional, and global levels. Dengue is a reemerging and uncontrolled disease. With dengue, there is a need for more scientific research on the local factors that affect the disease system and the relationships among those factors. There is also a need to develop new or improved dengue control approaches (2). In this paper, the situation of scientific research on dengue is analyzed for the developing country of Costa Rica. Although dengue has become the most important vector-borne disease in Costa Rica over the last decade, published scientific research dealing with the local situation is scarce (3). This could be due to various factors such as the historical and political context and limited financial and human resources. Filling this gap in Costa Rica and other developing countries would benefit local control programs and help efforts around the world to develop best practices for dengue prevention and control. Making this new knowledge broadly available could help improve the global dengue situation.